Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset containing 3823660 species occurrences available in GBIF matching the query: { "OccurrenceStatus" : [ "is Present" ] } The dataset includes 3823660 records from 54582 constituent datasets: Please see https://www.gbif.org/occurrence/download/0250289-220831081235567 for full list of all constituents.
Keywords: GBIF; biodiversity; species occurrences